PROTOTYPE SISTEM PEMANTAU KUALITAS UDARA BERBASIS RASPBERRY PI - zulhelman (Politeknik Negeri Jakarta, 2021)
Particulate Matter is an air pollutant substance that surrounds humans both indoors and outdoors. Humans cannot see or know the levels of pollution particles in the air and air quality without tools. Therefore, a prototype